PERSELISIHAN HUBUNGAN INDUSTRIAL AKIBAT PEMUTUSAN HUBUNGAN KERJA DI PT TORGANDA MEDAN (Studi Kasus Putusan Perkara Nomor 263/Pdt.Sus-PHI/2021/PN. Medan) - Yohanes Suhardin; Serilus Sapardi Duha (Universitas Katolik Santo Thomas Medan, 2025)
The purpose of this study is to find out the consideration of the Panel of Judges at the Industrial Relations Court (PHI), at the Medan District Court which stated that the actions of PT. Torganda is an act that violates Article 156 paragraph (4) letter b of Law Number 13 of 2003 concerning Manpower and to find out the legal consequences against PT. Torganda who terminated the employment relationship. The legal research method used is a normative legal research method that uses secondary data as the main data source. Secondary data collection is carried out by document study, namely research conducted by looking for data in the form of case verdict Number 263/Pdt.Sus-PHI/2021/PN/Mdn. The data obtained is processed and analyzed qualitatively, juridically, normatively. Conclusions are drawn by an inductive method, meaning that the author draws conclusions from specific to general. The results of this study explain that the Termination of Employment (PHK), carried out by PT. Torganda as Defendant I, and PT. Togos Gopas as Defendant II, against Nancy Ardhina Tambun as Plaintiff. The layoffs carried out by the Defendants are an act that violates Law Number 13 of 2003 concerning Manpower, as stated in the consideration of the Panel of Judges. Then the legal consequences for the parties in the decision of case Number 263/Pdt.Sus-PHI/2021/PN/Mdn regarding industrial relations disputes regarding termination of employment. The Defendants were sanctioned with severance and severance to pay the Plaintiff's normative rights in cash and at once.